2012
DOI: 10.1037/a0027304
|View full text |Cite
|
Sign up to set email alerts
|

An ecological analysis of the effects of deviant peer clustering on sexual promiscuity, problem behavior, and childbearing from early adolescence to adulthood: An enhancement of the life history framework.

Abstract: This study proposes the inclusion of peer relationships in a life history perspective on adolescent problem behavior. Longitudinal analyses were used to examine deviant peer clustering as the mediating link between attenuated family ties, peer marginalization, and social disadvantage in early adolescence and sexual promiscuity in middle adolescence and childbearing by early adulthood. Specifically, 998 youth and their families were assessed at age 11 years and periodically through age 24 years. Structural equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(129 citation statements)
references
References 83 publications
4
120
0
5
Order By: Relevance
“…Using this long-term prospective design, we were able to suggest (and find evidence for) developmental pathways from early peer risk factors to risky sexual behavior. Probing deeper into mechanisms that could account for children’s progression from peer rejection to risky sexual behavior, some scholars have suggested that children who are marginalized by the peer group adapt by organizing into deviant peer groups which then create social contexts for early and risky sexual behavior (Dishion, Ha, & Véronneau, 2012). This progression was supported using data from our whole sample, but the mechanisms appeared to differ by gender.…”
Section: Discussionmentioning
confidence: 99%
“…Using this long-term prospective design, we were able to suggest (and find evidence for) developmental pathways from early peer risk factors to risky sexual behavior. Probing deeper into mechanisms that could account for children’s progression from peer rejection to risky sexual behavior, some scholars have suggested that children who are marginalized by the peer group adapt by organizing into deviant peer groups which then create social contexts for early and risky sexual behavior (Dishion, Ha, & Véronneau, 2012). This progression was supported using data from our whole sample, but the mechanisms appeared to differ by gender.…”
Section: Discussionmentioning
confidence: 99%
“…Unpredictable environments at ages 0-5 predicted a fast life strategy at age 23, including increased risk and sexual behavior; however, neither harsh nor unpredictable environments at ages 6-16 predicted the same, suggesting early childhood instability may be a crucial developmental antecedent of adult risk behaviors (Simpson et al, 2012). Recent research also suggests that family-level socioeconomic disadvantage is related to deviant peer relationships in adolescence, which in turn contributes to sexual promiscuity (Dishion, Ha, and Véronneau, 2012). In at least one study, SES was positively associated with age at menarche; poorer girls reached menarche at earlier ages (James-Todd et al, 2010).…”
Section: Father Absence and Menarchementioning
confidence: 99%
“…This measure was based on data collected in high school, because only a small subset of at-risk participants had answered such questions in middle school. A strong correlation ( r = 0.72) existed between middle school and high school socioeconomic status (Dishion, Ha, & Véronneau, 2012). …”
Section: Methodsmentioning
confidence: 99%